ANALISIS PENENTU KEBERKESANAN INSTITUSI WAQF : STUDI KASUS MANAJEMEN WAKAF DI PROVINSI RIAU - Saib, Khaidir; Harwina, Yulia (Eko dan Bisnis: Riau Economic and Business Review, 2021)
Waqf has a social function that can provide great benefits to the community, both Muslims and non-Muslims if it can be managed productively and optimally. Even though the government has supported the production of waqf by issuing Law Number 41 of 2004 concerning Waqf. Since the issuance of the regulation, there has been no significant progress in managing waqf in a productive direction that can develop the people's economy. Basically, waqf is something that must be produced that produces economic value, but in essence not many waqf are managed productively for economic empowerment. The research methodology uses qualitative methods. This method was chosen to ensure that the reviewer can understand the concept and can see the problem from various angles, especially from the inner point of the phenomenon itself. This is because qualitative studies are more understanding, describing and explaining phenomena (Merriam, 1998) in Mohd Fuad (2006). The findings of this study reveal that the waqf management system in Riau Province is still traditional, Nazir in managing waqf assets does not work full time, unpaid side work, is not touched by socialization, waqf management is still consumptive and unprofessional.